2006
DOI: 10.1111/j.1574-6941.2006.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical distribution and ecological ranges of benthic cyanobacteria in East Antarctic lakes

Abstract: For the first time, the cyanobacterial diversity from microbial mats in lakes of Eastern Antarctica was investigated using microscopic and molecular approaches. The present study assessed the biogeographical distribution of cyanobacteria in Antarctica. Five samples were taken from four lakes spanning a range of different ecological environments in Larsemann Hills, Vestfold Hills and Rauer Islands to evaluate the influence of lake characteristics on the cyanobacterial diversity. Seventeen morphospecies and 28 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
157
5
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(178 citation statements)
references
References 51 publications
10
157
5
6
Order By: Relevance
“…These valleys are considered to be the coldest, most arid deserts on Earth (Cowan et al, 2002;Doran et al, 2002). In general, most of the mineral soils of the valley floors lack any visible cyanobacterial or algal growth, whereas biomass is more apparent in glacial streams and lake margins (Taton et al, 2006a). There has been considerable debate on assembly and viability of biotic communities in Dry Valley soils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These valleys are considered to be the coldest, most arid deserts on Earth (Cowan et al, 2002;Doran et al, 2002). In general, most of the mineral soils of the valley floors lack any visible cyanobacterial or algal growth, whereas biomass is more apparent in glacial streams and lake margins (Taton et al, 2006a). There has been considerable debate on assembly and viability of biotic communities in Dry Valley soils.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is their presence in Antarctic lakes and ponds that have attracted the most interest and led to detailed research into their taxonomy (morphological and molecular), community structure, biogeographical distribution and physiology (for example, Vincent et al, 1993;Taton et al, 2003Taton et al, , 2006ade los Ríos et al, 2004;Jungblut et al, 2005;Novis and Smissen, 2006). Recent molecular-based studies on these systems have revealed a higher diversity than that documented by morphological methods and identified potentially endemic Antarctic species (Taton et al, 2003(Taton et al, , 2006a. In contrast, the edaphic cyanobacterial communities of Antarctica have received less attention (Broady, 1996;Cavacini, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The polar regions therefore provide a unique opportunity to test biogeographic patterns of microbial diversity, providing predictors/indications of the future consequences of environmental change. The survival strategies and dispersal limitations, genetic identity and endemic character of polar microorganisms and, thus, their resilience and sensitivity are still under discussion (Vincent, 2000b;Taton et al, 2006;Jungblut et al, 2010;Vyverman et al, 2010). A comprehensive exploration of these microbial features using consistent methodology and sampling has been difficult to date due to the remoteness and inaccessibility of the polar regions.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-organisms form an interesting test case in the light of the refugium hypothesis in that they are expected, within the limits of their environmental tolerance, to show ubiquitous distribution patterns as a result of their virtually unlimited dispersal capacity (but see ongoing discussion on microbial biogeography in, for example, Martiny et al 2006). Molecular studies of cyanobacteria, using 16S rRNA gene sequencing, suggest that most isolates have a long association with the Antarctic environment (Taton et al 2003(Taton et al , 2006. Likewise, morphological studies on diatoms suggest that in some areas at least 40 per cent of the species are Antarctic endemics (Schmidt et al 1990;Sabbe et al 2004;Spaulding et al in press).…”
Section: Introductionmentioning
confidence: 99%